Comparative analysis of replicative properties of phylogenetically divergent, Argentinean BoHV-4 strains in cell lines from different origins - Morán, Pedro Edgardo (2019)
Bovine gammaherpesvirus 4 (BoHV4) is a member of the family Herpesviridae. In Argentina, BoHV4 was isolated and characterized in 2007 from samples of aborted cows. Argentinean isolates are highly divergent and are classified as: Genotype 1(Movar-like), Genotype 2 (DN599-like) and Genotype 3 (a novel group). The aim of this study was to comparatively evaluate the biological characteristics of six Argentinean BoHV4 field isolates in cell lines from different origins. All strains induced productive infection in the cell lines used, with different degrees of permissiveness. A direct relationship among the times of appearance of cytopathic effect, the growth kinetics, the size of the lysis plaques and the virulent-like behaviour in vitro could not be established. However, although slight, there are differences in the biological behaviour of the BoHV4 fields isolates analyzed. This variability is independent of their genetic classification but would be conditioned by the nature of the infected cells.